Bangladesh : Can Child Stimulation Messages Be Added to an Existing Platform for Delivering Health and Nutrition Information? - World Bank (World Bank, Washington, DC, 2017)
Development institutions and governments agree on the need to start early when it comes to children’s healthy development. Early childhood is a critical time for both the brain and body, and it’s important that children receive appropriate nutrition, health, stimulation and socio-emotional support in this period. But child development programs can be expensive and complicatedto deliver—especially when they include home visits to show caregivers how to stimulate healthy development—and it’s still not clear how best to design and deliver cost-effective programs in low-income areas. For example: Can information about best practices for keeping children healthy and stimulated successfully be delivered through established programs, like cash transfers or health services? What sort of training and mentoring is needed for successful home visits and can these be made cost-effective? The Government of Bangladesh is working with a variety of partners on initiatives to improve early childhood development and provide the country’s youngest citizens with a good start. Save the Children, an international non-governmental organization,designed and implemented a pilot program to provide new mothers with child development information during their visits to community health clinics and during regular home visits by health workers and family welfare assistants. The World Bank’s Strategic Impact Evaluation Fund (SIEF) supported an evaluation of the program to test the impact of adding this child stimulation component to a national nutrition program. The evaluation found that almost all families that received the program’s services, including informational cards on child development and picture books, reported using them, and their children showed small to modest gains in cognitive, linguistic and physical development compared with children whose families were not offered the program. The results show that it is possible to supplement existing health and nutrition programs with an additional component to improve children’s cognitive development in the early years, before they start any formal school program. However, almost 50 percent of households didn’t get the materials as expected, underscoring the challenges of using an already existing system of government community clinics and community outreach to deliver additional services. As policymakers in Bangladesh and in other countries seek successful approaches for supporting healthy child development, this evaluation provides promising evidence that the health sector can be used to improve young children’s development but also a cautionary lesson in the challenges of broadening existing health programs to include other components.